Needs Analysis of Student’s Worksheets to Improve Numerical Literacy Skills for Students of SMP Negeri 4 Yogyakarta, Indonesia - Miralda, Dara; Marhaeni, Nafida Hetty; Dwikarini, Mediarita (Indonesian Journal Education, 2022)
Numerical literacy ability is an important 21st century ability possessed by students. Teaching materials that have not integrated these abilities need to be developed. For this reason, the purpose of this study is to examine the needs of LKPD to improve students' numerical literacy ability. The type of research used is descriptive qualitative. The population used in this study was class VIII SMP Negeri 4 Yogyakarta, while the sample was class VIII.C SMP Negeri 4 Yogyakarta. Data collection techniques in this study used interview techniques, questionnaires, and students' numerical literacy test results. The results of the study showed that: (1) as many as 87% of students were interested if mathematics lessons were packaged in the form of LKPD; (2) based on the numeracy literacy test as many as 69% of students in the medium category and 14% in the low category; (3) as many as 37% of students are embarrassed to ask the teacher about subject matter that is not understood and affects the activity of students in the classroom. In addition, students want the LKPD to be blue and contain material, practice questions, and assignments. This study concludes that teaching materials using LKPD need to be applied to improve students’ numerical literacy ability